Determinan Perilaku Ibu Dalam Imunisasi Dasar Pada Anak Usia 12-23 Bulan - Lailatul Rahmawati; Widya Rizki Septianingtyas (ARTERI : Jurnal Ilmu Kesehatan, 2020)
The immunization program for infants aims to get every baby to get a complete basic immunization. Basic immunization status in children can be influenced by several factors related to community behavior towards immunization. The role of mothers in the immunization program is very important because in general, the parenting responsibility is given to parents, especially mothers. The Jelbuk and Klatakan health centers have the lowest complete basic immunization coverage in Jember in 2015 and 2016. The purpose of this study is to analyze the determinants of maternal behavior in basic immunization in children aged 12-23 months. This type of research is analytic observational with a cross-sectional research design. This research was conducted in the working area of ​​the Health Centers in Jelbuk and Klatakan in August-September 2017. Data collected from 100 mothers who had children aged 12-23 months. The sampling method is cluster random sampling. The results of the study using logistic regression tests showed that the level of knowledge and attitudes affected the basic immunization status of children aged 12-23 months with p-values ​​of 0.002 and 0,000, respectively. Knowledge and attitude of the mother are factors that can influence the completeness of basic immunization, therefore it is recommended to health workers to improve health promotion, especially about immunization so that basic immunization coverage can be increased and the risk of diseases that can be prevented by immunization can be reduced.